2017
DOI: 10.5455/ijlr.20170807065402
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin E, selenium and increased energy allowance on steroids and reproductive performance in transition period of crossbred cattle

Abstract: The present study was designed to bring out the effects of antioxidant and increased energy allowance on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
(27 reference statements)
1
2
0
Order By: Relevance
“…Smith et al, (1973) and Corah et al, (1974) demonstrated that estradiol increased linearly from one month prepartum and showed peak level at parturition, thereafter decreased at one day postpartum and remained at basal level until first postpartum estrus Corah et al, (1974) reported non-significant effect of energy level on plasma estrogen at transition period in cows. Similar finding was obtained by Khatti et al, (2017) with supplementation of high energy diet with Vitamin E and Se in the serum of crossbred cows.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Smith et al, (1973) and Corah et al, (1974) demonstrated that estradiol increased linearly from one month prepartum and showed peak level at parturition, thereafter decreased at one day postpartum and remained at basal level until first postpartum estrus Corah et al, (1974) reported non-significant effect of energy level on plasma estrogen at transition period in cows. Similar finding was obtained by Khatti et al, (2017) with supplementation of high energy diet with Vitamin E and Se in the serum of crossbred cows.…”
Section: Resultssupporting
confidence: 87%
“…In support of present results, Kamada and Hodate (1998) found that Se supplementation increased plasma progesterone concentration by 22% as compared to control in the postpartum cows which was attributed to the antioxidant effects and decreased amount of lipid peroxides (LPO) in the cells Atilia et al, (2015). However, Khatti et al, (2017) reported no marked effect of high energy diet supplemented with Vitamin E and Se on serum progesterone concentration during periparturient period. Further Ganie et al, (2014) also observed that Se supplementation had no effect on serum profile of reproductive steroids in buffalo heifers (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation